Guidelines for promoting accessibility in buildings through home automation - Vieira, Diego Vieira; Silva, Erick Santos da (Brazilian Journal of Science, 2022)
With the growing number of people with disabilities and the difficulties faced in carrying out daily activities, home automation has proved to be an alternative to promote accessibility in buildings. However, such a design solution has not been widespread, due to factors such as the high cost of implementation and the absence of skilled labor. Another issue to be highlighted is the low dissemination of its operation to the population. In view of the scenario described, this work carried out interviews with people with visual impairments, residing in the city of Maringá/Pr, with the objective of verifying their perceptions regarding home automation. It was also an objective of the research to disclose the benefits of the application of technology as a tool to help carry out day-to-day activities. The text had as methodological steps, the literature review, the construction of questionnaires (research instrument) and interviews. As a result, it was noticed that the relationship between the project professionals and the owner represents the basis for improving accessibility in the development of the layout of the home and that the adoption of technological solutions can enable better performance of buildings (minimize operating costs).